International Cooperation over Green Taxes: On the Impossibility of Achieving a Probability-One Gain - Thomas Aronsson; Kenneth Backlund; Karl-Gustav Löfgren (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper concerns international coordination of environmental taxation.The main contribution of the paper is to provide a frame-work for dynamiccost benefit analysis of environmental tax reforms in a global economy withtransboundary environmental problems. We show that the welfare effects ofgreen tax reform in a multi-country economy may differ substantially fromearlier results associated with representative agent models, where thetransboundary aspect of the environmental problems is neglected.
Keywords: 330; environmental taxation; global external effects.